ASPEK KEPERILAKUAN DALAM AKUNTANSI KEUANGAN - Muliawati . (Bina Ekonomi, 2012)
Financial accounting is conducted by accountant of each operating company. There are many alternative methods and approaches to choose in financial accounting. The final product of financial accounting is financial report. For a listed company in capital market, annual financial report must be audited by independent auditor, in order to give assurance that the company’s financial position and performance is presented fairly. Audit procedures require a lot of auditor’s judgment in all material respects. User of financial report will count on information in the financial report to support their economic decision making. Every decision and judgment made by accountant, auditor, and user of financial report is all about behavioral aspect in financial accounting. This article discusses about the development of behavioral accounting, the correlation between behavioral accounting and financial accounting, and the recent behavioral research in financial accounting.Keywords: Behavioral Accounting, Financial Accounting